Analysis of Grief in Dustin Thao's You've Reached Sam - Icha Widyaningtyas; Ambar Andayani (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study analyzes the experience of grief by Julie in Dustin Thao's You've Reached Sam. This study uses psychological theory, the stage of Grief by Elisabeth Kübler-Ross & David Kessler. The focus of this research is discusses the cause of Julie’s grief, the grief stages on Julie and the effect of grief on Julie. This study uses qualitative research with psychological approach. The results show that the cause of Julie's Grief is the stress of losing a loved one. The death of her boyfriend has been a source of deep grief for Julie throughout her life. In the denial stage, Julie is so shocked that she did not expect her boyfriend's death to be the result of an accident. In the anger stage, Julie confronts with a profound sense of anger and frustration. In the bargaining stage, Julie hopes that the person Julie lost can somehow return to her life and things can go back to normal. In the depression stage, Julie experiences profound sadness and a sense of emptiness and loneliness. In the acceptance stage, Julie realizes the need to accept her boyfriend's death as a permanent reality and reestablish herself in her previous life.